Design and construction of greenhouse with control and supervision computerized of temperature, humidity and intensity of light - del Carpio Salinas, Jorge Alberto (2006)
When beginning the project outlines to solve some of the problems that arise in the hothouses, as the high temperature and kit of high costs, with base a previous experience in a prototype much smaller. The other parameters are important but no so decisive as the temperature and they are the relative humidity and the illumination. For such end we built a hothouse type tunnel of 50 m2, (it is considered as minimum profitable area) redrew and built the electromechanical kit of control that consists of electronic kit of control with microcontroller and where the algorithms of control PI were programmed and Fuzzy Logic; also the set called Cooler Humidify and Heater Illuminator that have double function in benefit of the farming. The electromechanical kit is reproducible to low construction costs and energy but it has a physical behavior a so much complex.